2016
DOI: 10.1542/peds.2015-1742
|View full text |Cite
|
Sign up to set email alerts
|

Cow's Milk Allergy and Bone Mineral Density in Prepubertal Children

Abstract: BACKGROUND AND OBJECTIVES: Recent data suggest that cow's milk allergy (CMA) has become more persistent, prolonging treatment via strict elimination of cow's milk products into a period of skeletal growth. The objectives of this study were to compare bone mineral density (BMD), vitamin D status, and dietary intakes of calcium and vitamin D between prepubertal children with persistent CMA and those with non-cow's milk food allergies (NCMA) as control subjects and to assess the use of and compliance to calcium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…A further study in children with persistent cow's milk allergy also found a lower BMD in this population but found no correlation between BMD and calcium and vitamin D intake in the group with cow's milk allergy. The authors of that study hypothesised that this could be explained by the high steroid use within the group with cow's milk allergy, which may impact on calcium absorption and that the source of calcium in the healthy controls originated mainly from dairy‐containing foods that also contain other bone nutrients such as magnesium, zinc, phosphorous and potassium . The most pressing clinical question is whether this can be corrected once children outgrow their allergy and therefore prevent a long‐term effect.…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%
“…A further study in children with persistent cow's milk allergy also found a lower BMD in this population but found no correlation between BMD and calcium and vitamin D intake in the group with cow's milk allergy. The authors of that study hypothesised that this could be explained by the high steroid use within the group with cow's milk allergy, which may impact on calcium absorption and that the source of calcium in the healthy controls originated mainly from dairy‐containing foods that also contain other bone nutrients such as magnesium, zinc, phosphorous and potassium . The most pressing clinical question is whether this can be corrected once children outgrow their allergy and therefore prevent a long‐term effect.…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%
“…At the same time, the vitamin D status assessed based on concentration of 25(OH) vitamin D in blood serum of children with allergy was not reduced compared with control subjects, but this group had a lower calcium intake. Furthermore, in approximately 50% of children with allergy, the use of calcium and vitamin D supplements was declared [28]. Numerous authors point to adverse effects of long-term milk-free diet in children with allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of bone mineral density (BMD) on CMPA was studied in small populations of pre-pubertal children and of young adults [16]. In lumbar spine, z-scores were lower in CMPA children (n = 52) than in controls [16]. Calcium intake respected the American Recommended Daily Allowance (RDA) in 39% of CMPA children vs. 74% of controls (p = 0.003).…”
Section: Micronutrients and Macronutrients Deficiencymentioning
confidence: 99%